The influence of physical activity on emotional management ability in college students: a chain mediating role of psychological resilience and health literacy - Qi Liu; Wei-dong Zhu; Hu Lou; Ding-you Zhang; Fan-zheng Mu; Xin-yu Zhang; Yu-han Li; Wen-hao Zhang; Mo-han He; Jia-qi ang Wang; Chen-xi Li; Hao-yu Li; et al. (BMC Public Health)
Abstract Objective This study aimed to investigate the impact of physical activity (PA) on emotional management ability (EMA) in college students and to analyze the chain mediating roles of psychological resilience (PR) and health literacy (HL) in the relationship between PA and EMA. Methods Demographic information was collected using a stratified, cluster, and multi-stage sampling method. Data on PA, PR, HL, and EMA among college students were collected using an online questionnaire. A total of 13,590 valid questionnaires were obtained. Results A significant positive correlation was found between PA and EMA in college students (r = 0.177, P < 0.01). PR and HL played significant mediating roles in the relationship between PA and EMA. The mediation effect consisted of independent mediation by PR and HL and a chain mediation effect between the two. The values of the independent mediation effects and the chain mediation effect were 0.011, 0.010, and 0.004, respectively. The chain mediation effect was lower than each of the individual mediation effects and showed a statistically significant difference compared to the mediation effect of HL (P < 0.05). Conclusion PA significantly enhances college students’ EMA through direct effects and a chain mediation pathway involving PR and HL. Coordinated interventions, including regular exercise, PR training, and health education, are recommended to optimize college students’ psychological health.